(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
A good and conducive learning environment coupled with supportive teachers enhances students’ academic performance. The influence of students’ assessments in learning spaces, teacher support levels on their academic performance in TLE during modular distance modality was investigated in this study. A concurrent-nested mixed methods design was used to confirm, cross-validate, or corroborate findings within a study. A total of ninety-four participants participated in the study to respond to the questionnaire. Six groups with ten members joined in a focus group discussion (FGD) in the qualitative analysis part to describe their experiences in their learning spaces and teachers’ support in the modular learning modality. Descriptive statistics such as frequency, means, percentages, and standard deviation were used to determine the students’ learning spaces and the level of teacher support. Multiple regression analysis was used to determine the influence of learning spaces and teacher support on students’ academic performance. Furthermore, four themes emerged from the qualitative analysis part of the study, namely: Conducive Environment; Enabling resources; Motivating and Making a follow up with students; and Providing clear instruction and explanation. The study recommends further empirical investigation on the challenges of the students during modular learning.